Implementasi LKPD PKn Berorientasi Keberagaman Budaya dalam Membentuk Sikap Toleransi Peserta Didik Kelas V di SDN 43 Cakranegara - Ananda Nabila; Ramdhani Sucilestari; Syudirman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the implementation of Civic Education (PKn) student worksheets (LKPD) oriented toward cultural diversity in shaping students’ tolerance attitudes at SDN 43 Cakranegara. This research uses a qualitative descriptive approach. The subjects consisted of fifth-grade teachers, fifth-grade students, and the school principal as supporting informants. Data were collected through observation, interviews, and documentation. The findings reveal that the culturally diversity-oriented LKPD integrated learning materials related to ethnic groups, regional languages, traditional houses, traditional dances, and the values of unity in diversity. During the learning process, students became more actively involved in discussions, participated in group activities, and showed respect for their classmates’ opinions. The implementation of LKPD also encouraged collaborative learning and created opportunities for students to interact with peers from different backgrounds. Nevertheless, several challenges were identified, such as unequal student participation and limited interaction among certain groups during classroom activities. In conclusion, the implementation of culturally diversity-oriented PKn LKPD contributed positively to creating a more inclusive and interactive learning environment in elementary school classrooms. The integration of cultural diversity themes in LKPD helped students experience learning activities that were contextual and relevant to their daily social lives. Therefore, teachers are encouraged to design more innovative and interactive LKPD to support active student engagement and strengthen character education values in the learning process.